Pengembangan Sistem Pengelolaan Nilai Kurikulum 2013 Berbasis Web di Madrasah Aliyah Nurul Mujtahidin Ponorogo - Siti Nur Wahidah Abroriyah; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Madrasah Aliyah Nurul Mujtahidin is one of a senior education institutions lie under the supervision of Ministry of Religion of the Republic of Indonesia. Since 2016 Madrasah Aliyah Nurul Mujtahidin has been applying Kurikulum 2013 as the basic curricula in its learning processes. The application of Kurikulum 2013 influences all learning activities, one of which is the scoring management. Homeroom teachers use Microsoft Excel to collect scores from subject teachers. Documents containing scores ​​which are transferred from one person to another frequently result in error-prone data. In addition, a heaps of separate documents containing different subject scores also results in difficulties in recapitulating students' final scores. A web-based Kurikulum 2013 scoring management system was developed to overcome these problems. The development of this system was done by applying waterfall software development model and used object oriented approach. This system has been tested by using unit, integration, and validation testing. White-box testing was used in unit and integration testing whereas validation testing was done by using black-box testing. Unit and integration testing give forth valid results for 3 unit samples and 3 integration samples. The result of validation testing shows that system is 100% valid for 52 functional requirements.